2004
DOI: 10.1111/j.1752-0606.2004.tb01235.x
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Intervention for Promoting Recovery From Extramarital Affairs

Abstract: The discovery or disclosure of an extramarital affair can have a devastating impact on partners, both individually and on the relationships. Research suggests that affairs occur relatively frequently in relationships and are a common presenting problem in couple therapy. However, despite their prevalence, there is little empirical treatment research in this area, and most therapists describe this problem as one of the more difficult to treat. In this study, we used a replicated case-study design to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
225
4
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(240 citation statements)
references
References 22 publications
5
225
4
6
Order By: Relevance
“…Snyder, Baucom & Gordon, 2008;Baucom et al, 2006). However, most of these clinical guidelines are not grounded in empirical research but based on clinical experience (Olson et al, 2002), and only two recent small-sample studies have looked into the efficacy of couple therapy treatment programmes for infidelity, providing first indicators that these programmes can be effective (Atkins, Eldridge, Baucom & Christensen, 2005;Gordon, Baucom & Snyder, 2004).…”
Section: Working With Infidelitymentioning
confidence: 99%
“…Snyder, Baucom & Gordon, 2008;Baucom et al, 2006). However, most of these clinical guidelines are not grounded in empirical research but based on clinical experience (Olson et al, 2002), and only two recent small-sample studies have looked into the efficacy of couple therapy treatment programmes for infidelity, providing first indicators that these programmes can be effective (Atkins, Eldridge, Baucom & Christensen, 2005;Gordon, Baucom & Snyder, 2004).…”
Section: Working With Infidelitymentioning
confidence: 99%
“…Despite the fact that these clinicians have created these models based on their clinical experiences through their work with couples, the efficacy of these interventions have only been explored using case-study designs. Aside from Gordon, Baucom and Snyder's (2004) treatment approach, where they integrated both the literature on traumatic response and interpersonal forgiveness in their conceptualization of treatment, these approaches do not appear to be well grounded in empirical research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also found that using forgiveness type interventions are clinically useful in that they help to reduce hostility and anger, increase empathy, and increase positive feelings for individuals that are coping with an interpersonal conflict. Additionally, Gordon, Baucom and Snyder's (2004) forgiveness model has been examined through a replicated case study Snyder et al, 2004). Gordon, Baucom, and Snyder examined six couples that entered and completed treatment that was designed to aid couples in their recovery from an affair.…”
Section: From Trauma To Forgivenessmentioning
confidence: 99%
See 2 more Smart Citations